Penerapan Sanksi terhadap Pelanggaran Etik Aparatur Sipil Negara: Studi Kasus Putusan PTUN Jakarta Nomor 170/G/2020/PTUN.Jkt - Ane Putri Marciesyah (Uniku Law Review, 2025)
This paper discusses the importance of sanctions for civil servants who violate discipline. In more depth, this article aims to analyze the legal framework of the State Civil Apparatus (ASN) ethics that regulates the types of violations and sanctions that have implications for institutional value crises, as well as the extent to which the application of ethical sanctions is effective in preventing and overcoming such crises. This research uses a juridical analysis method with a normative legal research approach. As a central case study, this research places the Jakarta Administrative Court Decision No. 170/G/2020/PTUN.Jkt. The results show that strict legal structures, including Law No. 5 of 2014 and Government Regulation No. 37 of 2004, expressly prohibit civil servants from becoming members of political parties as a form of affirmation of neutrality. Violations of neutrality are a form of non-compliance with the code of ethics that result in severe disciplinary sanctions. The application of the Dishonorable Dismissal (PTDH) sanction by the defendant agency (Minister of Communication and Information) in Decision No. 170/G/2020/PTUN.Jkt. is considered effective from a legal and administrative perspective. This effectiveness is measured by the firmness of the institution's stance in prioritizing neutrality and creating a strong deterrent effect, which is a collective preventive measure to maintain the institution's image. However, law enforcement still faces obstacles, such as a lack of socialization and understanding among direct superiors regarding disciplinary oversight.